Peran Guru Fikih dalam Memotivasi Belajar Siswa di MTS Baitur Ridha Kecamatan Bahorok Langkat - Sabilla Rahma Syari; Hadi Saputra Panggabean (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
Fiqh is a branch of Islamic science that discusses the laws of sharia that regulate the lives of Muslims. The subject of Fiqh in schools has an important role in shaping students' understanding of Islamic teachings, but is often considered difficult and uninteresting by students. Therefore, this study aims to analyze the role of teachers in creating an effective learning atmosphere in the subject of Fiqh at MTs Baitur Ridha, Bahorok Langkat District. This study uses a qualitative method with a descriptive approach. Data were obtained through observation, interviews, and documentation to understand teacher strategies in increasing students' interest in learning and the obstacles faced in the learning process. The results of the study show that teachers not only act as teachers, but also as motivators who build students' enthusiasm for learning. Interactive methods such as discussion and practice are more effective than monotonous lecture methods. In addition, strategies such as question and answer methods and the use of technology such as computers and infocus have been shown to increase student engagement. However, there are still obstacles such as students' lack of interest in Fiqh material which is considered theoretical and monotonous, as well as limited variations in teaching methods. Interaction between teachers, schools, and parents also plays a role in supporting the effectiveness of learning.